ESRA19-0042 TSPO agonist RO5–4864 alleviates neuropathic pain and promotes remyelination in the sciatic nerve. (30th August 2019) - Liu, X; Ma, B; Ma, K
Abstract : Background and aims: Our previous study reported the analgesic effects of translocator protein (TSPO) in the spinal cord. However, its mechanism in the peripheral nervous system (PNS) is poorly understood. This study aimed to explore the distribution of TSPO in the dorsal root ganglion (DRG) and the possible mechanisms in PNS. Methods: A rat model of spared nerve injury (SNI) was conducted. Rats received a single intrathecal injection of TSPO agonist Ro5-4864. the behavior analyses were conducted. the expressions of TSPO, p-ERK and BDNF in the DRG were all analyzed. Two myelin regeneration proteins (P0 and PMP22) activations in the sciatic nerve were assayed. Results: TSPO signals were primarily colocalized with neurons and activated in DRG after SNI. Ro5-4864 exerted remarkable analgesic effects compared with the SNI group (P<0.01). After intrathecal administration of Ro5-4864 on Day 3, the expression of TSPO in the ipsilateral DRG was significantly increased on Day 7(P<0.01) but decreased on Day 14 (P<0.05) compared with the same point in time in the SNI group. Ro5-4864 also inhibited the activation of p-ERK1 (P<0.01), p-ERK2 (D7: P<0.01, D14: P<0.05), and BDNF (P<0.05) in the DRG. Meanwhile, Ro5-4864 further accelerated the expression of P0 and PMP22. Conclusions: Ro5-4864 could alleviate neuropathic pain and attenuate p-ERK and BDNF activation in DRG. Furthermore, Ro5-4864 stimulated the expression of myelin regeneration proteins which may also be an important factor against neuropathic pain development. TSPO may present a novel target for the treatment of neuropathic pain both in the central and peripheral nervous systems.